Successful talent development in track and field: considering the role of environment - Hwenriksen, K.; Stambulova, N.; Roessler, K. K. (Scandinavian Journal of Medicine & Science in Sports, 2010)
Track and field includes a number of high-intensity disciplines with many demanding practices and represents a motivational challenge for talented athletes aiming to make a successful transition to the senior elite level. Based on a holistic ecological approach, this study presents an analysis of a particular athletic talent development environment, the IFK Växjö track and field club, and examines key factors behind its successful history of creating top-level athletes. The research takes the form of a case study. Data were collected from multiple perspectives (in-depth interviews with administrators, coaches and athletes), from multiple situations (observation of training, competitions and meetings) and from the analysis of documents. The environment was characterized by a high degree of cohesion, by the organization of athletes and coaches into groups and teams, and by the important role given to elite athletes. A strong organizational culture, characterized by values of open co-operation, by a focus on performance process and by a whole-person approach, provided an important basis for the environment's success. The holistic ecological approach encourages practitioners to broaden their focus beyond the individual in their efforts to help talented junior athletes make a successful transition to the elite senior level.